Legal Protection of Children and Women Victims of Trafficking Crimes - M. Richul Firdaus; Junifer Dame Panjaitan (Jurnal Restorasi : Hukum dan Politik, 2023)
As we know, in Indonesia the protection of human rights (HAM) is very concerning. This can be seen from the many human rights violations. Examples of human rights violations are discrimination and are acts of violence. Human trafficking is one of the human rights violations that occur in Indonesia. The data recorded that children and women are the groups most often victimized in cases of criminal acts. Victims of human trafficking are not only for things whose purpose is sexual exploitation such as prostitution, victims become exploitation in other forms such as forced servants or forced labor and slavery. There are many problems in the form of manipulation in this kind of exploitation, especially against children and women due to the many criminal acts in human trafficking. Children and women, who deserve proper treatment, instead become material for exploitation for various purposes in many specific respects. The rise of human trafficking cases in Indonesia is also evidence that the legal conditions for respect and protection of human rights, especially human trafficking in Indonesia, are still insufficient to protect them